On the difference in valence electron plasmon energy and density of states between beta- and cubic-Si3N4 - Egdell, R; Henrich, V; Bowdler, R; Sekine, T (American Institute of Physics, 2003)
Core and valence level photoemissionspectra of β- and cubic-Si3N4 have been measured under monochromatic AlKα excitation. Strong satellites to high binding energy of the core lines are shown to arise from excitation of valence electron plasmons during the photoemission process. An increase in the plasmonenergy from 23.45 eV for β-Si3N4 to 26.10 eV for cubic-Si3N4 is of the magnitude expected from the 26% increase in the valence electron density associated with the shock-induced β-to-cubic phase transition. The measuredvalence banddensity of states for cubic-Si3N4 is in agreement with theoretical calculations.